Analysis of the Potential and Readiness of Schools in the Implementation of the Independent Curriculum - Pujiati Pujiati; Nurdin Nurdin; Rahmawati Rahmawati; Riyan Yuliyanto (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2026)
Curriculum reform is a strategic effort to improve the quality of education and the readiness of human resources, and its success depends on its implementation at the classroom level. This study aims to analyze the institutional potential and preparedness of educational units to implement the Independent Curriculum in Lampung Province. The research uses a quantitative descriptive approach with a survey method, involving 55 teachers and 66 students from 11 Senior High Schools (SHS). Data were collected through questionnaires supported by observations and interviews. The research results show that schools have high potential in terms of input and pedagogical readiness, including teacher competence, mastery of differentiated learning, support from the school ecosystem, implementation of the Pancasila Student Profile Strengthening Project, and adequate facilities. However, the implementation's effectiveness is still hindered by structural constraints, particularly the high administrative burden and limited teacher time management. Therefore, institutional strengthening is needed through collaborative socio-pedagogical strategies, such as peer mentoring and transforming MGMP into an active and sustainable learning community.